Generating Sustainable Wealth from Mozambique's Natural Resource Boom - Blanco Armas, Enrique (World Bank, Washington, DC, 2014)
This policy note aims to contribute to a national debate on the management of natural resource revenues. This policy note, part of a broader analytical program that seeks to inform macroeconomic and fiscal policy making in Mozambique to maximize the benefits from natural resource extraction, presents a series of recommendations on managing natural resource revenues. It assumes that the Government of Mozambique will chose to frontload public investments and spend a large share of the revenue from natural resources to meet the country's vast development needs. The policy note is divided in three sections. Section one discusses some of the challenges involved in responsibly managing resource revenues and key factors to consider in developing the fiscal policy framework. Section two presents a simulation exercise to illustrate how a fiscal policy framework that frontloads public spending can be implemented in Mozambique. Section three concludes the discussion and summarizes recommendations for enhancing fiscal and resource management in Mozambique.